Enhancing The Achievement Of Class Iii Students Through Environmental Use As A Learning Source Of Ips In Sd Negeri 29 Koto Panjang - Sri Jalita (Fakultas Sastra Universitas Ekasakti, 2017)
IPS is a field of knowledge excavated from everyday practical life in society. Therefore, the teaching of social studies that is not sourced to the community, is unlikely to achieve the goals and objectives of IPS lesson. Related to this research, the researcher is interested in the problems concerning the utilization of the environment as a learning resource, which is formulated in the research title. Researchers believe if teachers do not know the development of children, the teacher will face difficulties in carrying out their duties, because teachers have ignored the potential of children, whereas if teachers forget the demands and needs of society, then the teacher will foster students in unrealistic dreams. Based on the above statement, it is deemed necessary to introduce, understand, develop and apply the learning model with the utilization of the environment as a source of IPS SD learning in order to improve learning achievement. Therefore, researchers are encouraged to conduct research with the title